PTU-013 Capsule Endoscopy in Young Patients with Iron Deficiency Anaemia. (17th August 2016) - Rondonotti, E; Yung, DE; Giannakou, A; Rosa, B; Toth, E; Lucendo, A; Sidhu, R; Beaumont, H; Ellul, P; Negreanu, L; Jiménez-García, VA; Plevris, JN; et al.
Abstract : Introduction: Recent data imply young pts (≤50 yrs) investigated with capsule endoscopy(CE) for iron deficiency anaemia(IDA) show higher diagnostic yield(DY) for sinister findings. We aim to investigate DY of CE in a large cohort of young IDA pts and factors associated with sinister pathology. Methods: Retrospective multicentre study (2010–2015); consecutive pts ≤ 50 yrs undergoing CE for IDA at 19 centres in 12 countries. Exclusion criteria: ongoing/previous gastrointestinal(GI) bleeding; age > 50 or <19; comorbidities associated with IDA e.g. inflammatory bowel disease, coeliac disease. Data retrieved: indication for SBCE, investigations before CE (Hb, MCV, GI endoscopies/imaging, coeliac biopsies/serology), medications (NSAIDs, antiplatelets, warfarin/heparin), findings and final diagnosis. Clinical findings were analysed by multivariate logistic regression, and Akaike Information Criterion was used to include or exclude predictors. Results: 389 pts (262 F/127 M; mean age 39.4±9.3 yrs) were recruited. 169 pts (43.4%) were excluded from further analysis because clinically relevant data were not available; 220 pts were included in final analysis. They were grouped according to final diagnosis: neoplastic pathology (11/220; 5.0%); non-neoplastic but clinically significant findings (60/220; 27.3%); normal/minimal findings (149/220; 67.7%). The most common non-neoplastic findings were angiodysplasias(22/60) and Crohn's disease(15/60). On multivariate analysis, MCV was associated with occurrence of neoplasia (OR: 0.96; 95%CI:0.93-0.99; p = 0.033), i.e. the odds of SB neoplasia increased 4% for every unit of decrease in MCV. Weak evidence existed for the association between use of antiplatelet drugs and risk of SB neoplasms (OR: 5.83; 95%CI: 1.0–34.0; p = 0.05). Conclusion: In IDA patients ≤50 years, overall DY of SBCE for significant findings is 32.3%. Around 5% are diagnosed with SB malignancy. In this cohort, lower MCV or antiplatelet use have been associated with higher DY for SB neoplasia or clinically significant findings on CE. References: 1 Koulaouzidis A, et al . The use of small-bowel capsule endoscopy in iron-deficiency anaemia alone; be aware of the young anaemic patient. Scand J Gastroenterol 2012;47 :1094–100. 2 Sidhu PS, et al . The utility of capsule endoscopy in patients under 50 years of age with recurrent iron deficiency anaemia: Is the juice worth the squeeze? Gastroenterol Res Prac 2015:948574 . Disclosure of Interest: E. Rondonotti: None Declared, D. Yung Grant/research support from: Dr Falk/ Core F1/F2 Award 2015, A. Giannakou: None Declared, B. Rosa: None Declared, E. Toth: None Declared, A. Lucendo: None Declared, R. Sidhu: None Declared, H. Beaumont: None Declared, P. Ellul: None Declared, L. Negreanu: None Declared, V. Jiménez-García: None Declared, J. Plevris: None Declared, A. Koulaouzidis: None Declared